Employment outcomes and the interaction between product and labor market deregulation: are they substitutes or complements? - Giuseppe Fiori; Giuseppe Nicoletti; Stefano Scarpetta; Fabio Schiantarelli (Institute for the Study of Labor (IZA), 2007)
This paper provides a systematic empirical investigation of the effect of product market liberalization on employment when there are interactions between policies and institutions in product and labor markets. Using panel data for OECD countries over the period 1980-2002, we present evidence that product market deregulation is more effective at the margin when labor market regulation is high. Moreover, there is evidence in our sample that product market deregulation promotes labor market deregulation. We show that these results are mostly consistent with the basic predictions of a standard bargaining model, such as Blanchard and Giavazzi (2003), extended to allow for a richer specification of the fall back position of the union and for taxation.
urn:nbn:de:101:1-2008040244
Keywords: 330; Deregulierung; Arbeitsmarktflexibilisierung; Beschäftigungseffekt; Lohnverhandlungstheorie; OECD-Staaten